Partisipasi Petani dalam Perlakuan Benih untuk Peningkatan Kualitas Bibit Tanaman Padi Sawah - Achdiyat; Irvan Varinto (Politeknik Pembangunan Pertanian Bogor, 2022)
Seed treatment is strived to secure and improve the growth and development of lowland rice plants. It is done because lowland rice plants’ production does not meet the expectations; the low productivity of lowland rice plants is 61.35 kW/ha/th/GKP. The study aims to describe the level of participation of farmers in seed treatment, analyze factors related to farmers' participation in seed treatment, and develop strategies to increase farmer participation. The study was conducted from April to July 2019 in Tambaksari District, Ciamis Regency, West Java. The target is farmers who are members of the farmer group with the commodity paddy. The total respondents were 71 farmers. Data was collected through semi-structured interviews with closed questionnaires and direct observation. Descriptive analysis is used to describe the level of farmer participation, while correlation analysis is used to find out factors related to farmer participation. Paddy farmers' involvement in seed treatment activities is included in the